Top Legal Risks and Regulatory Trends Facing Canadian Optometrists - WLG, Gowling (Canadian Journal of Optometry, 2018)
Doctors of Optometry are subject to many of the same legal risks and trends facing most regulated health professionals in Canada. These legal exposures range in scale from College investigations into an optometrist’s billing practices to seven-figure lawsuits alleging that an optometrist failed to appropriately diagnose and refer a patient for further investigation and treatment. This article uses information gained through calls made by insured optometrists to the Canadian Association of Optometrist (CAO)’s Insurance Program pro bono legal services hotline along with over 15 years of program claims data to provide an overview of common legal risks and regulatory trends affecting the profession.